"The Course of a Particular": Names and Narrative in the Works of Joseph Mitchell. (March 2015) - Adams, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Joseph Mitchell (1908–1996) wrote about unusual New York people for The New Yorker. For journalists like Mitchell, a name identifies a "who, " an essential component of a news story even more central to a profile. For Mitchell, however, names are strangely significant: they are textual loci at which narratology, epistemology, and ontology enmesh. The balance of these categories and their mutual engagements are idiosyncratic and define Mitchell's style. It is a style that proves how intellectually and emotionally powerful journalistic uses of names can be. A catalog of names confirms one's knowledge of phenomena by reconstituting it narratively. Naming in narrative is a mode of knowing one's experience. But maybe the stakes are higher: maybe names insist on the reality of the things named. Onomastic specificity underwrites our ontological confidence, but the ontological significance of names is never wholly persuasive, not even when justified within a narrative. Confronting its limitations, as Mitchell did, brings on melancholy. Joy and melancholy wrought of names are intimately related in Mitchell's style and integral to it, as, after all, they are to living.